Physico-geotechnical properties of peat and its stabilisation - Prabir, Kumar Kolay; Md Aminur, Rahman (Thomas Telford Services Ltd, 2016)
This paper describes the physical and geotechnical properties of tropical peat treated with different types of stabilisers. Fly ash (FA), quicklime (QL) and ordinary Portland cement (OPC) were used as stabilisers. The amount of FA, QL and OPC added to the peat samples was in the range of 5–20, 2–8 and 5–20%, respectively. Various physical and geotechnical tests have been conducted to characterise the peat samples. Unconfined compressive strength (UCS) tests were conducted on untreated and treated peat samples. The results show that the UCS value increases with the increase of all stabilisers used and with the curing period. The UCS tests were also conducted on the peat samples with a combination of waste FA and QL to study the combined effects of the stabilisers. This research established different correlations between the physical and geotechnical properties of original peat and UCS results on treated peat samples with different types of stabilisers. Geotechnical engineers can refer to these correlations to determine the bearing capacity of treated peat for long-term curing periods. In addition, scanning electron microscopic studies were conducted on original/untreated and treated peat samples to investigate the microstructure of the samples.